PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE KEPALA BERNOMOR UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA PADA MATERI KERJASAMA NEGARA-NEGARA ASIA TENGGARA DI KELAS VI SDN. NO. 013/XI SUMUR ANYIR TAHUN 2016/2017 - Alis Khamri (Jurnal Ilmiah Universitas Batanghari Jambi, 2018)
The research conducted is a classroom action research that aims to increase the student’s activity in the class and student’s learning outcome on the subjects of Civic Education by using Numbered Heads Together Model. This research was conducted in two cycles, namely cycle I and cycle II. Each cycle consists of four activities, namely planning, execution, observation, and reflection. This research involves nine students of sixth class in SDN. No. 013/XI Sumur Anyir, Sungai Penuh City, Jambi Province. Research was started from January to May in 2017. Student’s learning outcome are seen from the average value in the class and student's learning completeness. The result of this research showed that Numbered Heads Together model can improve student's learning outcomes. This result is evidenced by the increase in student learning outcomes which are seen from the increase in the average value in the class and student's learning completeness before and after the action is implemented. In addition to learning outcomes, students also experience an increase also in terms of student activity in the class. The observation results indicate that all students have been listening to the teacher's explanation actively, forming a heterogeneous group, and willing to discuss answers with a group of friends. Most students have also dared to communicate the results of their group discussions and respond to other group presentations.Keywords: civic education, conceptual understanding, elementary school students, learning outcomes, Numbered Heads Together